Caffeine, but not bicarbonate, improves 6 min maximal performance in elite rowers - Christensen, P. M.; Petersen, M. H.; Friis, S. N.; Bangsbo, J. (Applied Physiology, Nutrition, and Metabolism, 2014)
This study examined the ergogenic effects in a 6 min maximal performance test (PT) on 12 elite rowers: 6 open-weight (mean ± SD; 25 ± 1 years, and 92 ± 3 kg) and 6 light-weight (25 ± 3 years, and 73 ± 6 kg), following supplementation with caffeine (CAF), sodium bicarbonate (SB), and the combination of both, in a double-blind randomized placebo (PLA) controlled design. PT was executed on 4 occasions, on separate days within a week, and in a non-fasted state, with standardized training being performed the day before PT. Protocols were as follows: (i) CAF, 3 mg/kg, 45 min prior to PT+calcium as SB-PLA; (ii) SB, 0.3 g/kg, 75 min prior to PT+dextrose as CAF-PLA; (iii) CAF+SB; and (iv) PLA; CAF-PLA+SB-PLA. The total distance in the CAF (1878 ± 97 m) and CAF+SB (1877 ± 97 m) was longer than in the PLA (1865 ± 104 m; P < 0.05) and SB (1860 ± 96 m; P < 0.01). The mean power in CAF (400 ± 58 W) and CAF+SB (400 ± 58 W) was higher than the PLA (393 ± 61 W; P < 0.05) and SB (389 ± 57 W; P < 0.01). In CAF and CAF+SB, power was higher (P < 0.05) relative to PLA in the last half (4-6 min) of PT. Trials with CAF were more effective in light-weight rowers (1.0% ± 0.8% improvement in distance; P < 0.05) than in open-weight rowers (0.3% ± 0.8%; P > 0.05). No difference between interventions was observed for readiness and stomach comfort before PT and perceived exertion during PT. This study demonstrates that caffeine ingestion does improve performance in elite rowing. In contrast sodium bicarbonate does not appear to be ergogenic, but it does not abolish the ergogenic effect of caffeine.